If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 5) * 8 = 72 Reorder the terms: (5 + 2x) * 8 = 72 Reorder the terms for easier multiplication: 8(5 + 2x) = 72 (5 * 8 + 2x * 8) = 72 (40 + 16x) = 72 Solving 40 + 16x = 72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 16x = 72 + -40 Combine like terms: 40 + -40 = 0 0 + 16x = 72 + -40 16x = 72 + -40 Combine like terms: 72 + -40 = 32 16x = 32 Divide each side by '16'. x = 2 Simplifying x = 2
| -36-52= | | 4.5-1.5(6m+2)=3 | | 7+3*4-1=39 | | 3y-4(y+2)=2(3y-2) | | -1-10(10r+6)= | | -3n-5n=8 | | 5x^2+5y=45 | | 3z-9=3 | | -2x+6=16 | | 7p=35 | | (x-5)(x-6)=6 | | 4x-7=7x-5 | | x^4-17x^2+52=0 | | 3a-15=-6 | | 3y/2=-6 | | 4x+20=53-2x | | y=7x^2-x+11 | | V^2-2v=4v+40 | | 17=(3x) | | 5x/6=30 | | 0.2x=10 | | 6x-18+4y-20=170 | | 8b+3-10b=2(b-2)+3 | | -3x+-7=-22 | | 2x-2-12=3x-3 | | 6gh-15h+10-4g= | | 12x-4=13x-5 | | x^3-20x^2+96x=0 | | -x-4x-7=-2x+5 | | -10-3b=3b+2(-8b-5) | | 6g+2gh+5h+15= | | x(x+-6)=40 |